Pengaruh Good Corporate Governance dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Moderasi - Sri Handoko Sakti; Krisnando Krisnando (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2019)
- This study aims to examine whether the influence of Good Corporate Governance is proxied by institutional ownership, an independent board of commissioners, and an audit committee as well as the size of the company that is moderated by financial performance on the value of the company in manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2015 -2017. This research uses descriptive quantitative research, which uses multiple linear regression-based methods with Eviews 10. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2017 period. The sample was determined based on the purposive sampling method, with a total sample of 18 manufacturing companies, so that the total observation in this study was 54 observations. The data used in this research is secondary data. Data mining techniques using methods carried out through the official sites www.idx.co.id and www.idnfinancials.com. Hypothesis testing using t test. The results of the study prove that Good Corporate Governance is proxied by institutional ownership, an independent board of commissioners, and an audit committee, as well as company size. institutional ownership has a significantly negative effect on firm value. This reflects the higher proportion of institutional ownership, the higher the pressure from various corporate investors to raise profits. While the independent board of commissioners, audit committee, and company size do not significantly influence the value of the company. This reflects that more and more members of the board of independent commissioners will cause difficulties in coordination between members of the board of independent commissioners and the audit committee and may hamper supervision. The impact of this is that the market gives a negative reaction and results in a decrease in the value of the company. Financial Performance does not moderate the relationship between institutional ownership, independent board of commissioners, and audit committee, as well as the size of the company against the value of the company in manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2017 period.